Issues pertaining to the official visit of the Deputy Director General - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
The document is a compilation of: a country profile of Guyana, its history, politics and administration, and international organizations and bilateral mission activities; profiles of government officials; technical cooperation programme 1989; and highlights of the 1989 budget speech. El documento es una compilación de: un perfil de país de Guyana, su historia, política y administración, organizaciones internacionales y actividades de misiones bilaterales; perfiles de funcionarios gubernamentales; programa de cooperación técnica 1989; y aspectos destacados del discurso sobre el presupuesto de 1989.